Citizenship Status and Contraceptive Method Use Among Latinx, Asian and Pacific Islander (API) Women in California - Angubeen G. Khan; May Sudhinaraset; Yasamin Kusunoki; Jessica D. Gipson (Journal of Immigrant and Minority Health, 2026)
Abstract Citizenship status confers rights and access to healthcare, yet little is known about how it impacts contraception use and type of method use. This study examined the role of citizenship status on contraceptive use among reproductive-aged (18–44 years), cis-gender Latinx and Asian and Pacific Islander (API) women. This study used the 2017–2020 waves of the California Health Interview Survey (CHIS). Inclusion criteria included cisgender, heterosexual Latinx and API women of reproductive age (18–44 years) who were at risk of becoming pregnant ( N = 3,027). Participants were classified into the following categories based on their citizenship status: non-citizens without a green card, legal permanent residents (LPRs), naturalized citizens, and U.S.-born citizens. We conducted bivariate analyses using Pearson’s chi-square tests and multivariable analyses using adjusted binomial logistic regressions to assess associations between citizenship status and use of any modern and reversible method of contraception and type of method used. Models were stratified by race/ethnicity. All analyses were weighted. Three-quarters (75.8%) of the sample were Latinx, 57.5% were U.S.-born citizens, 16.3% were naturalized citizens, 10.6% were LPRs, and 15.7% were non-citizens without a green card. There were no significant differences in the type of contraception method use by citizenship status among Latinx. Among API, naturalized citizens had lower odds of any use and condom use and naturalized citizens and U.S.-born citizens had higher odds of using pill or other hormonal methods and IUD or implant compared to non-citizens without a green card. This study makes important contributions in understanding the role of citizenship status as a social determinant of reproductive health for Latinx and API in California.